(untitled) (ModaPalavra e-periódico, 2023)
Due to the large amounts of waste generated by the agro-industry and the pressures for changes in the fashion industry supply chains, the opportunity to develop new materials is constantly expanding. The present study aims to develop a handbag using Canary melon rind (Cucumis melo var. inodorus) treated via biotechnological methods. Additionally, it discusses the importance of identity and positioning for new materials of the future. The rinds were treated with cellulase enzyme and subsequently subjected to sewing tests. The design project was specifically developed for constructing the bag using the treated material. Enzymatic results showed characteristics of malleability and resistance. The design project was aligned with the specific requirements for the most efficient sewing of the material. The bag prototype resulted in a product that enhances the material’s capacity and contributes to the development of new materials in the fashion industry.